Role of Bladder Hydrodistention and Intravesical Sodium Hyaluronate in the Treatment of Interstitial Cystitis - Yang, Jin-Yi; Wei, Wei; Lan, Yu-Long; Liu, Jun-Qiang; Wang, Hai-Bo; Li, Shao (Urology Journal, 2015)
Purpose: To evaluate the clinical efficacy of bladder hydrodistention and intravesical sodium hyaluronate in the treatment of interstitial cystitis (IC). Materials and Methods: Twenty-one patients with IC received intravesical sodium hyaluronate therapy under nerve block or intravenous anesthesia. Bladders were perfused with 100 cmH2O perfusion pressure and expanded for 10 min and were later injected with 40 mg/50 mL sodium hyaluronate through the catheter. After 1 h, the perfusion fluid was released. Perfusion was applied once per week, 4 to 6 times as a course of treatment. Results: Under anesthesia, the average bladder capacity was 191.62 ± 88.67 mL, and after bladder expansion, the bladder capacity reached 425.33 ± 79.83 mL (P = .000). There were 2 suspected bladder ruptures after bladder expansion at 6.5 min and 7.2 min. After 10 min of bladder expansion, there were 19 cases of significantly gross hematuria. After treatment, the catheters of 17 patients were removed at 24 h; for the 2 cases of hematuria, catheters were removed at 72 h and for the 2 cases of suspected bladder rupture, catheters were removed after 4 days. After catheter removal, the pain threshold significantly decreased, and the maximum urinary output increased slightly. Compared with values before treatment, the day before the second injection of sodium hyaluronate, the frequency of urination decreased significantly (32.8 vs. 18.5 times/24 h), the maximum urinary output increased significantly (86.7 vs. 151.9 mL), the pain decreased significantly (8.7 vs. 3.0), and the O'Leary-Sant IC score and quality of life score were significantly decreased (30.0 vs. 17.0 and 5.9 vs. 2.4, respectively) (P = .000). Conclusion: Bladder hydrodistention under anesthesia for patients with severe intractable IC produces immediate effectiveness; sodium hyaluronic infusion can alleviate frequent urination and pain, and the efficacy was positively correlated with the duration of treatment.